Links between self-regulation patterns and prosocial behavior trajectories from middle childhood to early adolescence: a longitudinal study - Ritgens, Carolin; Bondü, Rebecca; Warschburger, Petra (Frontiers in Psychology, 2024)
Prosocial behavior that conforms to social norms and serves the good of others requires particularly high self-regulatory competences, because it is often in contrast with one's own interests. It is unknown which self-regulatory competences are particularly important for prosocial-behavior development and whether they may distinguish between children on different prosocial-behavior trajectories. This longitudinal study examined differences in self-regulatory competences, including inhibition, emotional reactivity, planning behavior, emotion regulation, working-memory updating, affective decision making, flexibility, and delay of gratification, between trajectories of prosocial behavior in 1,657 German 6-to 13-year-olds (52% female). LCGA suggested four trajectories of stable high, stable low, increasing, and decreasing prosocial behavior. MANOVAs showed differences between trajectories in inhibition and emotional reactivity at all three measurement points, as well as planning behavior at the second measurement point. Early patterns of these selfregulatory skills may help identifying children at risk for impaired long-term prosocial-behavior development and should primarily be addressed by prevention and intervention measures.